A Review on the Pathogenesis and Clinical Management of Placental Site Trophoblastic Tumors - Feng, Xuan; Wei, Zhi; Zhang, Sai; Du, Yan; Zhao, Hongbo (Frontiers in Oncology, 2019)
Placental site trophoblastic tumor (PSTT) is a rare type of gestational trophoblastic disease originating from the intermediate trophoblast. Compared with hydatidiform mole, invasive hydatidiform mole and choriocarcinoma, the diagnosis of PSTT is more complicated and lacks specific and sensitive tumor markers. Most PSTT patients demonstrate malignant potential, and the primary treatment of PSTT is hysterectomy. However, metastasis occasionally occurs and even causes death in a small number of PSTT patients. Most PSTT patients are young women hence fertility preservation is an important consideration. The major obstacle for PSTT patient prognosis is chemotherapy resistance. However, the current understanding of the pathogenesis of PSTT and clinical treatment remains elusive. In this review, we summarized the research progress of PSTT in recent years from three aspects: mechanism, clinical presentation, and treatment and prognosis. Well conducted multi-center studies with sufficient sample sizes are of great importance to better examine the pathological progress and evaluate the prognosis of PSTT patients, so as to develop prevention and early detection programs, as well as novel treatment strategies, and finally improve prognosis for PSTT patients.